Trends in Indonesia’s Literacy Rate from 2015 to 2022: Disparities Analysis and Projections toward the 2030 SDGs - Yosua Damas Sadewo; Mikael Febrianto Owen; Edwar Joist; Anica Vatta Hanesty (Institut of Shanti Bhuana, 2025)
Literacy rate (Angka Melek Huruf/AMH) is a key indicator of educational development and Sustainable Development Goals (SDGs) Target 4.6, which aims to achieve universal literacy by 2030. This study analyzes trends in Indonesia’s literacy rate from 2015 to 2022 and projects progress toward the SDGs 2030 target. A quantitative approach was employed using a least squares trend analysis based on secondary data from Statistics Indonesia (BPS). The analysis covers four main dimensions—area of residence, gender, economic quintile, and province—across three age groups (15 years and above, 15–24 years, and 15–59 years). The results indicate a steady national increase in literacy, rising from 95.22% in 2015 to 96.35% in 2022, with projections approaching universal literacy by 2030. Nevertheless, persistent disparities remain evident, particularly between urban and rural areas and across provinces, with Papua consistently recording the lowest literacy rates. These findings suggest that while Indonesia is likely to achieve national-level literacy targets, substantial subnational inequalities persist. Therefore, targeted and context-specific policy interventions are required to ensure equitable literacy outcomes and the inclusive achievement of SDGs Target 4.6.